Bolivia: A Gasified Democracy - Assies, Willem (European Review of Latin American and Caribbean Studies, 2004)
In October 2003 a wave of popular protest  brought down the Sánchez de Lozada government  in Bolivia. The intention to export natural gas to  the United States and Mexico triggered the protests, but actually stood for widespread discontent  with the Sánchez de Lozada government, the  preceding governments and the economic policies  pursued since 1985. The events belie the opinion  of various students of the Latin American democratic transitions who held that Bolivian democracy  was on its way towards consolidation and suggest that the recent inquiries into the quality of Latin  American democracies may point a way ahead in  rethinking democracy in the region. Taking such  assessments as a reference, this article reviews the  ‘gas war’ and looks at the Bolivian political regime as it has functioned over the past decades. It  will be argued that the ‘pacted democracy’, that  until now sustained institutionality, and the economic model adopted in 1985 have excluded an  important part of the population, both in political terms and where poverty alleviation and equity is  concerned. Increasing popular protest has been  met with increasing repression, which gradually  turned Bolivia into a ‘democradura’, or a ‘gasified  democracy’ that relies on teargas and bullets to  uphold itself. At present the country finds itself at  a crossroads. It either may reinvent democracy or  become an institutionalized ‘democradura’. Resumen: Bolivia: una democracia gasificadaEn octubre de 2003 una ola de protesta popular  llevó a la caída del gobierno de Sánchez de Lozada en Bolivia. La intención de exportar gas natural a los Estados Unidos y México gatilló dichas  protestas, aunque en realidad reflejaron un descontento general con el gobierno Sánchez de  Lozada, los gobiernos anteriores y las políticas  económicas implementadas desde 1985. Los  sucesos desmienten la opinión de varios analistas  de las transiciones democráticas latinoamericanas  que afirmaban que la democracia boliviana estaba  en camino hacia la consolidación y sugieren que  las investigaciones recientes acerca de la calidad  de la democracia en América Latina señalan nuevas pautas para repensar la democracia en la región. Tomando tales evaluaciones como punto de  referencia este artículo describe la ‘guerra del gas’  y examina la forma de funcionar de la democracia  boliviana durante las últimas décadas. Se argumentará que la ‘democracia pactada’, que durante  este período aseguró la institucionalidad, y el  modelo económico adoptado en 1985, excluyeron  a importantes sectores de la población, tanto en  términos políticos cómo en lo que se refiere al  alivio de la pobreza y la equidad. Protestas crecientes fueron reprimidas con una violencia  igualmente creciente, lo que paulatinamente convirtió a Bolivia en una ‘democradura’ o una ‘democracia gasificada’ – que necesita de gas lacrimógeno y balas para sustentarse. De momento, el país se encuentra en un cruce de caminos; o se reinventa la democracia o se institucionaliza la  ‘democradura’.